Pengaruh Sinbiotik terhadap Penurunan Kadar C-Reactive Protein Serum Pasca operasi pada Anak Appendisitis Komplikata - Vita Indriasari; Bustanul Arifin Nawas; Dikki Drajat Kusmayadi; Rizki Diposarosa (Jurnal llmu Bedah Indonesia, 2014)
Background. Appendicitis is the most common cause of acute abdomen in children. Complicated appendicitis due to perforation associated with high morbidity. Several perioperative conditions fascilitated systemic inflammation and postoperative infectious complication. Synbiotic has a potential effect on reducing inflammatory response which reflected with lower serum c-reactive protein (CRP) level, so that the infectious complication could be avoided. Aim.This study aimed to observe the effect of synbiotic on postoperative serum CRP level reduction in children with complicated appendicitis. Method. A randomized double blind study was done in 26 children with com- plicated appendicitis. The subjects were divided into synbiotic and placebo groups. Synbiotic was given 1 time preoperatively and continued 5 days afer surgery. Serum CRP level were examined preoperatively (CRP 0), postoperative day 1 (CRP 1), and 6 (CRP 6). Statistical analysis was done with Independent-t test (p<0,05 considered significan)t. Result. The mean age of the patients was 9,85 years. The onset of abdominal pain was 3,92 days. The mean reduction of CRP 0 –CRP 6 between synbiotic and placebo group was 65,21% ± 31,37 SD vs 78,29% ± 12,39 SD, p=0,073; and the mean reduction of CRP 1–CRP 6 was 73,54% ± 22,04 vs 74,56% ±17,58, p=0,897. Wound infection was lower in synbiotic group (7,69% vs 38,46%). Conclusion. There was no difference in postoperative serum CRP level reduction between synbiotic therapy and placebo in children with compli- cated appendicitis